Adiponectin receptor agonist reduces broiler hepatic lipid deposition - Tan, Wenhao; Jiang, Kunyu; Zhang, Yuhan; Gao, Hang; Tang, Xingyi; Jiang, Sha (Frontiers in Veterinary Science, 2025)
To investigate the effects of AdipoRon on fatty liver syndrome (FLS) in chicken, we used a corticosterone (CORT)-induced fatty liver model in Cobb broilers in vivo and fat emulsion-induced model in Leghorn male hepatoma cells (LMH) in vitro. In the in vivo study, eighteen 33-day-old male Cobb broilers were randomly assigned to three groups: control group (CONT, vehicle), corticosterone-treated group (CORT, 4 mg/kg), and corticosterone with AdipoRon-treated group (CORT-AR, 4 mg/kg and 0.2 mg/kg, 1 time/1 day) for 5 days. The results showed AdipoRon reduced CORT-induced increase in liver crude fat content (p < 0.05), increased protein expressions of peroxisome proliferator-activated receptor α (PPARα) (p < 0.05) and adiponectin (ADPN) (p < 0.05), and suppressed the protein expressions of Acetyl-CoA carboxylase 1 (ACC) (p < 0.05) and phosphorylated c-Jun N-terminal kinase 1 (p-JNK1) (p < 0.05) in the liver. In the in vitro study, LMH cells were divided into control (CN), fat emulsion (FE, 10%), and FE + AdipoRon (4 μM) group (FE-AR). AdipoRon reduced FE-induced lipid accumulation (p < 0.05), decreased the protein expression of ACC and tumor necrosis factor-alpha (TNF-α), and enhanced PPARα, the phosphorylation of adenosine 5′-monophosphate-activated protein kinase (AMPK), and carnitine palmitoyl transferase 1 (CPT-1) (p < 0.05). In conclusion, AdipoRon effectively reduces hepatic lipid deposition in CORT-induced FLS broilers, likely through PPARα activation and inhibition of lipid synthesis via ACC downregulation.